Benchmarking Treatment Response in Tourette's Disorder: A Psychometric Evaluation and Signal Detection Analysis of the Parent Tic Questionnaire. Issue 1 (January 2018) - Ricketts, Emily J.; McGuire, Joseph F.; Chang, Susanna; Bose, Deepika; Rasch, Madeline M.; Woods, Douglas W.; Specht, Matthew W.; Walkup, John T.; Scahill, Lawrence; Wilhelm, Sabine; Peterson, Alan L.; Piacentini, John
Abstract: This study assessed the psychometric properties of a parent-reported tic severity measure, the Parent Tic Questionnaire (PTQ), and used the scale to establish guidelines for delineating clinically significant tic treatment response. Participants were 126 children ages 9 to 17 who participated in a randomized controlled trial of Comprehensive Behavioral Intervention for Tics (CBIT). Tic severity was assessed using the Yale Global Tic Severity Scale (YGTSS), Hopkins Motor/Vocal Tic Scale (HMVTS) and PTQ; positive treatment response was defined by a score of 1 ( very much improved ) or 2 ( much improved ) on the Clinical Global Impressions – Improvement (CGI-I) scale. Cronbach's alpha and intraclass correlations (ICC) assessed internal consistency and test-retest reliability, with correlations evaluating validity. Receiver- and Quality-Receiver Operating Characteristic analyses assessed the efficiency of percent and raw-reduction cutoffs associated with positive treatment response. The PTQ demonstrated good internal consistency (α = 0.80 to 0.86), excellent test-retest reliability (ICC = .84 to .89), good convergent validity with the YGTSS and HM/VTS, and good discriminant validity from hyperactive, obsessive-compulsive, and externalizing (i.e., aggression and rule-breaking) symptoms. A 55% reduction and 10-point decrease in PTQ Total score were optimal for defining positive treatment response. Findings help standardize tic assessment and provide clinicians with greater clarity in determining clinically meaningful tic symptom change during treatment. Highlights: Psychometric and signal detection analyses of the Parent Tic Questionnaire were performed. The scale showed good internal consistency, convergent and discriminant validity, and excellent test-retest reliability. A 55% reduction and 10-point decrease in PTQ Total score defined positive treatment response. Findings clarify clinically meaningful tic symptom change during treatment.